URINE STABILIZATION AND TREATMENT USING LACTIC ACID FROM FRUIT AND VEGETABLE PEEL FERMENTATION: A POTENTIAL SOURCE OF NITROGEN FERTILIZER - Khamala, Tabitha Nekesa (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
<div class="min-h-[20px] text-message flex flex-col items-start whitespace-pre-wrap break-words [.text-message+&]:mt-5 juice:w-full juice:items-end overflow-x-auto gap-2" dir="auto" data-message-author-role="assistant" data-message-id="f3b1989e-8794-4ee6-9205-5091626d7d43"> The study investigated the use of lactic acid obtained from the anaerobic fermentation of specific fruit and vegetable wastes (mango, orange, banana, pineapple, and cabbage) for urine stabilization. It focused on optimizing lactic acid production by altering fermentation temperatures and waste-to-water ratios and assessing its efficiency in treating urine over various time periods. In Kenya, large amounts of fruit and vegetable waste are inappropriately disposed of, contributing to environmental contamination and odors. Meanwhile, urine contains valuable nitrogen that might be used as fertilizer, but its usefulness is hampered by urea hydrolysis, resulting in nitrogen loss, ammonia production, a higher pH, and potential pathogen growth such as E. coli. The study used anaerobic fermentation methods to extract lactic acid from washed and cut waste samples blended with water in 1:1 and 1:2 ratios (waste to water). Fermentation lasted three days at temperatures of 34°C, 37°C, and 40°C, followed by sieving, centrifugation, and spectrophotometric measurement. The optimal parameters for lactic acid generation were determined to be 37 °C with a waste-to-water ratio of 1:1 (absorbance of 1.188 and concentration of 0.848). The produced lactic acid was then mixed with fresh urine at a 1:2 ratio (lactic acid to urine) and stored to determine its effectiveness in stabilizing urine over four, seven, and ten days. The results showed that lactic acid produced at 37 °C greatly increased nitrogen content in treated urine while dramatically lowering pH levels, suggesting its strong stabilizing impact. Most MacConkey agar plates showed no growth of E. coli, except for samples treated for four days and those treated with lactic acid produced at 34 °C, demonstrating lactic acid's ability to limit microbial activity. This work provides a viable and cost-effective solution for on-site sanitation systems, specifically urine-diverting dry toilets, using simple sample preparation techniques that can be widely adopted.